PERANCANGAN SISTEM INFORMASI TRANSAKSI PENYEWAAN WEDDING ORGANIZER PADA CV.DENIS CITRA MANDIRI BEKASI - Ade Wiwid Taniah; Sri Harjunawati (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
In today's era of globalization, information technology is speeding up, among other things, computers that are devices created to simplify human work. This tool is progressing rapidly both in hardware and software. Organizations, especially organizations in the form of business-oriented companies can take advantage of this technological advancement, not least with CV. Denis Citra Mandiri, a company engaged in the rental of a wedding organizer. The existing system in a CV. Denis Citra Mandiri is still done manually, ranging from recording client hiring wedding organizer, until the storage of other data related to the process of leasing transactions up to the making of reports, making it possible at the time of the process going wrong in the Recording, inaccuracy of reports made and delays in searching for necessary data. Membutukan once the existence of an information system that supports and provide satisfactory service for the customer. To overcome these problems, researchers try to make the design of wedding organizer rental transaction system on a CV. Denis Citra Mandiri by using web programming. By using this design is expected to Program that can solve the problems that exist in this company. In addition, using this design is expected to achieve effective and efficient activities so that the company's profits will increase.